Співвідношення політичної участі і політичного функціонування у політичному процесі - Мацкевич, Роман Миколайович; Мацкевич, Роман Николаевич; Mackevych, R. (My University, 2010)
In the article the questions of correlation of political participation categories and political functioning in a political process are examined. Thus under political participation actions, undertaken by the members of socio-political community on individual or group basis on purpose to have influence on the process of formulation or acceptance of political decisions, realization of public policy or choice of political ﬁ gures at any level of power are understood.
Мацкевич Р. М. Співвідношення політичної участі і політичного функціонування у політичному процессі / Р. М. Мацкевич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 243-249.
Keywords: співвідношення політичної участі і політичного функціонування у політичному процесі; соотношение категорий политического участия и политического функционирования в политическом процессе; the ratio of the categories of political participation and political functioning in the political process